Synthesis and Evaluation of Antibacterial Activity of 2-Acetamido-4-acet(4'-aryl-3'-chloro-2'-oxo-azetidinyl)amino thiazole - Krishna Rao, Gopal; Sanjay Pai, P.N.; Bagavant, G.; Singh Bansal, Inderjit (Asian Journal of Chemistry, 2016)
Arylidene derivatives of ethyl 2-acetamidothiazole-4-acetate were synthesized by condensing an ester of ethyl 2-acetamidothiazole-4-acetate and hydrazine hydrate followed by reaction with the respective aldehydes. These were characterized on the basis of IR, NMR and mass spectral data. Final compounds were evaluated for antibacterial activity against the organisms Pseudomonas aeruginosa, Bacillus subtilis, Escherichia coli and Staphylococcus aureus.